THEORETICAL BASIS OF THE USE OF ANALYTICAL OPERATIONS IN INTERNAL AUDIT (Marketing Journal, 2025)
This article analyzes the significance and effectiveness of using analytical procedures in the internal audit process of business entities. Analytical procedures enable internal auditors to identify and assess risks, examine the internal control system, an d ensure the accuracy and reliability of financial reporting. The article discusses key analytical methods such as trend analysis, ratio analysis, regression analysis, and Benfordʼs Law analysis. Additionally, it explores the stages of applying analytical procedures in internal auditing, their advantages, and potential limitations. The study substantiates the possibility of risk management, efficiency improvement, optimal resource utilization, and achieving strategic goals through analytical procedures. The article highlights the importance of analytical methods in ensuring a more efficient and precise internal audit process.
Keywords: analytical procedures; internal audit; internal control system; international auditing standards; financial reporting; trend analysis; ratio analysis; regression analysis; Benfordʼs Law analysis